2019
DOI: 10.1115/1.4042808
|View full text |Cite
|
Sign up to set email alerts
|

Blackbox Optimization for Aircraft Engine Blades With Contact Interfaces

Abstract: In modern aircraft engines, reduced operating clearances between rotating blade tips and the surrounding casing increase the risk of blade/casing structural contacts, which may lead to high blade vibration levels. Therefore, structural contacts must now be accounted for as early as in the engine design stage. As the vibrations resulting from contact are intrinsically nonlinear, direct optimization of blade shapes based on vibration simulation is not realistic in an industrial context. A recent study on a blade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
(68 reference statements)
2
10
0
Order By: Relevance
“…It is important to note, however, that the reduction is particularly striking for the first torsion mode, while interactions seem to occur mainly with the first bending mode. This confirms recent results showing that an efficient improvement of the blade's robustness may involve taking into account the dynamic clearance of more modes than only the first bending mode [56].…”
Section: Dynamic Clearancesupporting
confidence: 91%
See 3 more Smart Citations
“…It is important to note, however, that the reduction is particularly striking for the first torsion mode, while interactions seem to occur mainly with the first bending mode. This confirms recent results showing that an efficient improvement of the blade's robustness may involve taking into account the dynamic clearance of more modes than only the first bending mode [56].…”
Section: Dynamic Clearancesupporting
confidence: 91%
“…The geometry of the reference blade can be modified either by acting on the MCA parameters of each profile, or by modifying the stacking line along which the profiles are positioned by varying the sweep and lean of the blade. Previous works have shown that modifying the stacking line has significant consequences on the aerodynamic performances of the blade [31,54,55] as well as on the blade's response to contact events [38,56]. Therefore, six new blades are defined by varying the sweep and lean to compare their responses to contact events with that of the reference blade.…”
Section: Re-designed Blades With Sweep and Lean Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the blade was optimized with respect to its clearance consumption [17]-which quantifies how the blade-tip/casing clearance evolves as the blade vibrates along one of its free-vibration modes-and much lower amplitudes of vibration were numerically predicted for the redesigned blade. Based on this work, a blade parameterization was later proposed for academic blade models and systematic optimization of these profiles with respect to their clearance consumption underlined the relevance of this criterion [18].…”
Section: Introductionmentioning
confidence: 99%